2020
DOI: 10.1186/s12891-020-03802-4
|View full text |Cite
|
Sign up to set email alerts
|

Infra-acetabular screw exited between ischial tuberosity and ischial spine is more suitable for Asian population: a 3D morphometric study

Abstract: Background Recently, the infra-acetabular screw has been proposed for use in treatment of acetabular fractures as a part of a periacetabular fixation frame. Biomechanical studies have shown that an additional infra-acetabular screw placement can enhance the fixation strength of acetabular fracture internal fixation. Currently, the reported exit point of the infra-acetabular screw has been located at the ischial tuberosity (Screw I). However, our significant experience in placement of the infra-acetabular screw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Gras et al [ 14 ] showed that the optimal angle between the axis of the corridor to the APP is 54.8°, that is, the fluoroscopy is performed at 35°. Liu et al [ 18 ] found that in contrast with the traditional IAS where the screw-out point is on the ischial tuberosity, placing the screw-out point between the ischial spine and the ischial tuberosity is more suitable for Asian people. At this time, the mean angle between the screw axis and the coronal plane is 75.2°, that is, the fluoroscopy is performed at 15°.…”
Section: Discussionmentioning
confidence: 99%
“…Gras et al [ 14 ] showed that the optimal angle between the axis of the corridor to the APP is 54.8°, that is, the fluoroscopy is performed at 35°. Liu et al [ 18 ] found that in contrast with the traditional IAS where the screw-out point is on the ischial tuberosity, placing the screw-out point between the ischial spine and the ischial tuberosity is more suitable for Asian people. At this time, the mean angle between the screw axis and the coronal plane is 75.2°, that is, the fluoroscopy is performed at 15°.…”
Section: Discussionmentioning
confidence: 99%